POST-MANDIBULAR FRACTURE OSTEOMYELITIS: : CASE REPORT AND LITERATURE REVIEW - Mendes Dourado, Murilo (Health and Society, 2021)
Osteomyelitis represents an inflammatory entity of the bone tissue with spinal cord involvement. Its etiology is multifactorial, presenting difficult diagnosis and complex treatment, being the prognosis, in most cases, unpredictable. Therefore, it is an inflammation of the medullary spaces caused by the decrease of the blood supply, leading to an ischemia and subsequent necrosis of the bone tissue. Although odontogenic infections are the most commonly involved in the onset of osteomyelitis, other situations also play a relevant role, such as: periodontal diseases, exodontia, and facial trauma. Treatment included combination of antibiotic therapy and surgical procedures. Although correct antibiotic therapy plays an important role in the success of the treatment, the surgical procedure is essential for the removal of the cause and possible bone sequestration formed by the infectious process. The objective of this work is to perform a review of the literature on Osteomyelitis and present two cases of Chronic Suppurative Osteomyelitis that emerged as a complication of mandible fracture. We observed that OSC caused after fracture of face presents clinical characteristics similar to those from odontogenic infection and that the treatment of choice is similar.